Portable storage and data loss - FARRELL, STEPHEN (IEEE, 2008)
Data loss or leakage occurs in many organizations, frequently with significant impacts, both in terms of incident-handling costs and of damage to the organization's reputation. In this paper, the author considers information leakage related to portable storage - for example, your laptop hard-disk - and what might best mitigate that. This article briefly considers some recent incidents, describe practical mitigation steps, and look at how we might plan, in advance, for handling such events.
PUBLISHED
Keywords: digital storage; data security